REMEDIASI MISKONSEPSI MATERI GAYA MENGGUNAKAN MODEL LEARNING CYCLE 5E BERBANTUAN MEDIA ANIMASI DI SMP - Hardi Safrianto; Haratua Tiur Maria Silitonga; Erwina Oktavianty (Universitas Tanjungpura, Prodi Pendidikan Fisika, 2022)
This research aimed to determine the effect of 5e learning cycle model in reducing students misconception on force concept in SMP Negeri 1 Jawai Selatan. This research was a pre-experimental with one group pretest-posttest design. This research use intact sample of class VIII C which consist of 28 students. The result of data analysis showed that students misconception before remediation was 78,34% in the all concept of force. Meanwhile, after remediation the misconception decrease by 20,34% to 58% of all concept. The result of McNemar significance test on df = 1 and α = 5% showed x2count > x2table, were equal to 15,91> 3,84. There was a conceptual change on the students significantly. The effect size of this research attain a high result d = 1,242. With the result, 5e learning cycle model assisted animation concept effective to remediated class VIII C student misconception on force concept in SMP Negeri 1 Jawai Selatan.